Pengaruh Perceived Social Support dan Regulasi Emosi Terhadap Subjective Well-Being pada Santri Mahasiswa - Derida Achmad Bil Haq; Hermien Laksmiwati; Miftakhul Jannah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study used a quantitative approach with a correlational associative design on 196 male students in the early adulthood phase at two Islamic boarding schools in Surabaya. The instruments used included the SWLS and PANAS to measure Subjective Well-Being (SWB), the MSPSS for Perceived Social Support (PSS), and the ERQ for Emotion Regulation (ER). The results of the Spearman correlation analysis showed that PSS had a strong positive relationship with SWB (ρ = 0.627, p < .001), while ER showed a moderate positive relationship with SWB (ρ = 0.537, p < .001). Non-parametric regression analysis with the bootstrap method showed that PSS (β = 0.742, p < .001) and ER (β = 0.511, p < .001) had a significant effect both partially and simultaneously on SWB, with a model contribution of 61.5% (R² = 0.615). These findings confirm that Perceived Social Support and Emotion Regulation are important predictors in improving the Subjective Well-Being of Islamic boarding school students. Practically, the results of this study contribute to the achievement of Sustainable Development Goals (SDGs) goal 3 (Health and Well-Being) by strengthening the mental health of the early adult age group, as well as SDGs goal 4 (Quality Education) by providing an empirical basis for the development of psychopedagogical interventions and sustainable social support systems in Islamic boarding school environments.